Three-Dimensional in Vivo Imaging of Green Fluorescent Protein-Expressing T Cells in Mice with Noncontact Fluorescence Molecular Tomography - Anikitos Garofalakis; Giannis Zacharakis; Heiko Meyer; Eleftherios N. Economou; Clio Mamalaki; Joseph Papamatheakis; Dimitris Kioussis; Vasilis Ntziachristos; Jorge Ripoll (Molecular Imaging)
Given that optical tomography is capable of quantitatively imaging the distribution of several important chromophores and fluorophores in vivo, there has been a great deal of interest in developing optical imaging systems with increased numbers of measurements under optimal experimental conditions. In this article, we present a novel system that enables three-dimensional imaging of fluorescent probes in whole animals using a noncontact setup, in parallel with a three-dimensional surface reconstruction algorithm. This approach is directed toward the in vivo imaging of fluorophore or fluorescent protein concentration in small animals. The system consists of a rotating sample holder and a lens-coupled charge-coupled device camera in combination with a fiber-coupled laser scanning device. By measuring multiple projections, large data sets can be obtained, thus improving the accuracy of the inversion models used for quantitative three-dimensional reconstruction of fluorochrome distribution, as well as facilitating a higher spatial resolution. In this study, the system was applied to determining the distribution of green fluorescent protein (GFP)-expressing T lymphocytes in a transgenic mouse model, thus demonstrating the potential of the system for studying immune system function. The technique was used to image and reconstruct fluorescence originating from 32 × 10 6 T cells in the thymus and 3 × 10 5 T cells in the spleen.